Pengaruh Kualitas Produk Dan Kualitas Pelayanan Terhadap Kepuasan Pelanggan Indihome - Bima, Ericho Arya; Pudjoprastyono, Hery (Akuisisi : Jurnal Akuntansi, 2023)
This study aims to determine how product quality and service quality affect Indihome customer satisfaction in Surabaya. Residents in Surabaya who use Indihome whose population is not explicitly known are the research population. Seventy Indihome users in Surabaya were selected as research participants through the Non Probability Sampling method and the Purposive Sampling approach. Data collection is done by sending questionnaires to respondents using Google Forms with an ordinal scale using a Likert scale with a score range of 1 to 5. Then with Partial Least Square (PLS) data analysis techniques, the data is processed by validity tests, reliability tests, structural model tests, and hypothesis tests. The findings show that quality positively and significantly impacts Indihome customer satisfaction in Surabaya, both in terms of product quality and service quality